Paleoclimatic modeling and phylogeography of least killifish, Heterandria formosa: insights into Pleistocene expansion-contraction dynamics and evolutionary history of North American Coastal Plain freshwater biota - Bagley, Justin C (BioMed Central, 2013)
BACKGROUND: Climatic and sea-level fluctuations throughout the last Pleistocene glacial cycle (~130-0 ka) profoundly influenced present-day distributions and genetic diversity of Northern Hemisphere biotas by forcing range contractions in many species during the glacial advance and allowing expansion following glacial retreat ('expansion-contraction’ model). Evidence for such range dynamics and refugia in the unglaciated Gulf-Atlantic Coastal Plain stems largely from terrestrial species, and aquatic species Pleistocene responses remain relatively uninvestigated. Heterandria formosa, a wide-ranging regional endemic, presents an ideal system to test the expansion-contraction model within this biota. By integrating ecological niche modeling and phylogeography, we infer the Pleistocene history of this livebearing fish (Poeciliidae) and test for several predicted distributional and genetic effects of the last glaciation. RESULTS: Paleoclimatic models predicted range contraction to a single southwest Florida peninsula refugium during the Last Glacial Maximum, followed by northward expansion. We inferred spatial-population subdivision into four groups that reflect genetic barriers outside this refuge. Several other features of the genetic data were consistent with predictions derived from an expansion-contraction model: limited intraspecific divergence (e.g. mean mtDNA p-distance = 0.66%); a pattern of mtDNA diversity (mean Hd = 0.934; mean π = 0.007) consistent with rapid, recent population expansion; a lack of mtDNA isolation-by-distance; and clinal variation in allozyme diversity with higher diversity at lower latitudes near the predicted refugium. Statistical tests of mismatch distributions and coalescent simulations of the gene tree lent greater support to a scenario of post-glacial expansion and diversification from a single refugium than to any other model examined (e.g. multiple-refugia scenarios). CONCLUSIONS: Congruent results from diverse data indicate H. formosa fits the classic Pleistocene expansion-contraction model, even as the genetic data suggest additional ecological influences on population structure. While evidence for Plio-Pleistocene Gulf Coast vicariance is well described for many freshwater species presently codistributed with H. formosa, this species demography and diversification departs notably from this pattern. Species-specific expansion-contraction dynamics may therefore have figured more prominently in shaping Coastal Plain evolutionary history than previously thought. Our findings bolster growing appreciation for the complexity of phylogeographical structuring within North America’s southern refugia, including responses of Coastal Plain freshwater biota to Pleistocene climatic fluctuations.